TAX POLICY AND INCOME INEQUALITY IN THE UNITED STATES, 1979–2007. (18th November 2014) - Bargain, Olivier; Dolls, Mathias; Immervoll, Herwig; Neumann, Dirk; Peichl, Andreas; Pestel, Nico; Siegloch, Sebastian
Abstract This paper assesses the effects of U.S. tax policy reforms on inequality over around three decades, from 1979 to 2007. It applies a new method for decomposing changes in government redistribution into (1) a direct policy effect resulting from policy changes and (2) the effects of changing market incomes. Over the period as a whole, the tax policy changes increased income inequality by pushing up the income share of high‐income earners (the top 20%). (JEL H23, H31, H53, P16)